A study on the printability properties of alkali-sized recycled papers - AYDEMİR, CEM (WALTER DE GRUYTER GMBH, 2016)
Recycled handsheets were prepared from old newspapers and old office papers with internal sizing applications of alkyl ketene dimer (AKD) emulsion at 0.5%, 1.0% and 1.5% addition levels as received basis. Handsheets made at 80 g/m(2) were air dried and oven dried as placed in drying rings followed by conditioning prior to testing. The contact angle, surface energy and drop volume changes of handsheets were carefully measured as well as used some offset printing applications. Freeness levels of pulp from newspapers and office papers were measured to be 65 and 45 SR degrees, respectively. It was confirmed that AKD sizing improved paper resistance against water and printing ink, and this was further improved with oven drying. Contact angle values obtained from oven-dried office papers and newspapers were in the range of 105 degrees-95 degrees and 85 degrees-75 degrees, respectively. Without drying, lowest contact angles from newspapers and office papers were recorded to be around 72 degrees and 37 degrees, respectively. Results were in agreement with surface energy values of samples which were around 60 mJ/m(2) for air-dried samples and over 30 mJ/m(2) for oven-dried handsheets. It was concluded that sizing actually improves print quality but may also increase colour change differences over time as represented by Delta E.
Keywords: colour change; print quality; recycled papers; sizing; surface energy; DROPLET; WATER; SURFACE